2001
DOI: 10.1074/jbc.m010847200
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive ERK1/2 Activation in Esophagogastric Rib Bone Marrow Micrometastatic Cells Is MEK-independent

Abstract: In this study, we examined the mitogen-activated protein kinase (MAPK) cascade in micrometastatic cell lines generated from rib bone marrow (RBM) of patients undergoing resection of esophagogastric malignancies. The molecular mechanism(s) involved in esophagogastric MAPK activation have not previously been investigated. Constitutive activation of both ERK1 and -2 isoforms was evident in each of the five RBM cell lines. Elk-1, a transcription factor activated by the ERK1/2 pathway was also found to be constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Phosphorylation is usually transient even in the continued presence of activating stimuli, indicating that protein phosphatases represent an important mechanism for MAPK control. Down-regulation of MKPs or resistance to dephosphorylation by MKPs is often observed in human tumors (36)(37)(38). Recent data show that Notch antagonizes EGF in developing C. elegans, and one mechanism is through up-regulation of LIP-1, a homologue of mammalian MAPK phosphatases (28).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation is usually transient even in the continued presence of activating stimuli, indicating that protein phosphatases represent an important mechanism for MAPK control. Down-regulation of MKPs or resistance to dephosphorylation by MKPs is often observed in human tumors (36)(37)(38). Recent data show that Notch antagonizes EGF in developing C. elegans, and one mechanism is through up-regulation of LIP-1, a homologue of mammalian MAPK phosphatases (28).…”
Section: Resultsmentioning
confidence: 99%
“…4B. (24,35,36). More recently, decreased expression of MKP-1 has been strongly associated with the advanced progression of human ovarian cancers (37).…”
Section: Exogenous Mkp-1 Phosphatase Activity Decreases Erk Phosphorymentioning
confidence: 99%
“…This may be attributable to elevated Ras-Raf-MKK1/2 signaling (20 -22). Nonetheless, constitutive activation of ERK1/2 has been reported to be independent of MKK1/2 and Raf-1 (23,24), and the mechanism by which sustained ERK1/2 activation occurs remains elusive. We recently reported that Pb(II) persistently stimulates ERK1/2 without activating JNK, p38, and ERK5 in CL3 human lung cancer cells and normal human fibroblasts, and sustained ERK1/2 signaling is essential for cellular nucleotide excision repair synthesis, anti-cytotoxicity, and anti-mutagenesis (25).…”
mentioning
confidence: 99%
“…This frequently depends on up-regulation of the RAS/ MEK cascade. However, constitutive ERK overexpression may also occur independently of the RAS/MEK signaling (10,11). Recent studies (12,13) indicate that prolonged activation of ERK promotes phosphorylation at the Ser 296 residue of its inhibitor, dual-specificity phosphatase 1 (DUSP1; also known as MAPK phosphatase-1).…”
Section: Introductionmentioning
confidence: 99%